THE THERAPEUTIC INTERVENTION OF MUROTTAL AL-QUR’AN IN OVARIAN CYST PATIENTS WITH ACUTE POSTOPERATIVE PAIN PROBLEMS - Hasnah; Muthahharah; Andi Riska Roswati; Nurul Fadhilah Gani (Jurnal Kesehatan, 2022)
Ovarian cyst is a sac filled with fluid in the ovary. Ovarian cysts are caused by impaired hormone production in the hypothalamus, pituitary and ovaries. The main function of the ovaries is to produce eggs or ova, to produce hormones (progesterone and estrogen), and to participate in regulating the menstrual cyst .Ovarium is common cause of gynecology morbidity in women. Therefore, need the best intervention to affected the symptoms. This study purpose to determine the effect of murottal Al-Qur'an therapy on patients with medical diagnosis of ovarian cysts with acute postoperative pain problems at Labuang Baji Hospital Makassar. The design of this study used a case study conducted with an evidence-based practice in nursing approach. After being given the nursing care process for 3 days, the results showed that murottal intervension helped reduce pain of postoperative ovarian cyst patients on the first postoperative day, the patient's pain scale was 4 (moderate) and until the 3rd day the patient's pain scale decreased to scale 1 (mild). The provision of non-pharmacological interventions, namely murottal therapy can reduce pain and the patient's grimacing decreases. In overcoming the problem of acute pain cannot walk alone, it is necessary to have other interventions, namely collaboration in providing analgesics.